ENZYMATIC TREATMENT OF PALM KERNEL CAKE IMPROVES INTESTINAL HEALTH, GUT MICROBIOTA AND IMMUNE SYSTEM OF BROILERS. - H. A. Aguzey; Z.H. Gao1; H.H. Wu; G.L. Cheng; Z.M. Wu; J.H. Chen; Z.L. Niu (Journal of Animal and Plant Sciences, 2020)
Palm kernel cake is a very important agro-industrial by-product from the production of palm kernel oil. It contains a lot of nutrients needed by chicken for growth and productivity but this potential is hindered because of the presence of mannan and other anti-nutritional factors. Mannans are made up of simple sugar D-mannose. Mannans comprise of a linear backbone of mannose residues joined by β-1, 4-mannosidic linkages comprising glucomannan, galactomannan and galactoglucomannan depending on carbohydrates or acid substitutions in the backbone. Enzymes have the ability to degrade this mannan component in order to make the nutrients available to the animals. Mannanoligosaccharides improve the development of small intestine of chicks during pre- and post-hatch periods, increasing the villi height, crypt depth and number of goblet cells per villus on the day of hatch. The activities of these enzymes help in increasing the population of beneficial microorganisms residing in the gastrointestinal tract of chicken. The surge in the beneficial microorganisms residing in the gastrointestinal region of chicken helps in boosting their immune system. Feeding palm kernel cake promotes growth and prevents diseases by boosting the immune system of broilers.
Keywords: Gut microbiota; immune system; enzyme; intestinal morphology; palm kernel cake